2013
DOI: 10.1155/2013/649142
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cd (II), Cu (II), and Zn (II) from Aqueous Solution onto Nitrogen‐Functionalized Desmostachya bipinnata

Abstract: A very simple means of nitrogen functional group grafting onto the backbone ofDesmostachya bipinnatais investigated, which is a sacrificial herb in the south Asian region particular to Hindu religion. This natural biomaterial is found to be very effective for metal binding, after treatment with hydrazine monohydrate. The present study explores a comparison of amination processes by considering several options. The maximum metal loading capacities for Cd, Cu, and Zn were found to be 76.80 mg/g, 72.10 mg/g, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, it was performed at varied pH conditions of 4, 5 and 7, for Cu(II), Pb(II) and Cd(II), respectively, to ensure that metal precipitations were avoided. All uptakes followed the usual adsorption phenomenon where sorption efficiency comparatively decreases with increasing initial concentration [9,15,[25][26][27][28][29].…”
Section: Isotherm Of Single Metal Solutionsmentioning
confidence: 78%
“…However, it was performed at varied pH conditions of 4, 5 and 7, for Cu(II), Pb(II) and Cd(II), respectively, to ensure that metal precipitations were avoided. All uptakes followed the usual adsorption phenomenon where sorption efficiency comparatively decreases with increasing initial concentration [9,15,[25][26][27][28][29].…”
Section: Isotherm Of Single Metal Solutionsmentioning
confidence: 78%
“…These materials have some comparative advantages in contrast to common sorbent materials. Some remarkable studies can be seen in Table 1 [15][16][17][18][19][20][21][22][23][24][25]. As seen in Table 1, there are researches all over the world, work on the understanding of the mechanisms of removing copper and cadmium ions through new sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their restricted functional sites, the adsorption of heavy metals on raw biosorbents was discovered to be less efficient. Functional groups such as carboxylate, hydroxyl, sulphate, phosphate, amide or amine have been found to be accountable for significant metal bindings on the biosorbents [ 63 ]. The intrinsic sorption property of all biosorbents is based on the concentration and configuration of effective groups on the sorbing surfaces.…”
Section: Carbohydrate Biopolymers Based Adsorbentsmentioning
confidence: 99%
“…Ghimire et al [ 63 ] in their work highlighted the necessity of utilizing functionalized biosorbents for the removal of heavy metals such as Cd 2+ and Zn 2+ . In their studies the functionalized biosorbents demonstrated good selectivity, and adsorption capacities.…”
Section: Carbohydrate Biopolymers Based Adsorbentsmentioning
confidence: 99%